2022
DOI: 10.17770/sie2022vol1.6809
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Implementation of Crossfit Tools in the Process of Physical Education of High School Pupils

Abstract: There is justified in the article the importance of the need to improve physical education process for high school students with CrossFit tools.There have occurred positive changes in high school students’ dynamics in the EG in functional indicators and physical preparation in the experiment condition.The optimization of physical education process for high school pupils with CrossFit tools. There were observed the indicators of physical condition of organism, physical preparation and experimentally checked the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Additionally, weight training programs have improved adolescents' self-efficacy (e.g., confidence in their ability to accomplish a task), self-esteem, self-perceptions, and overall confidence [19][20][21], which was reflected in our findings for increased confidence and self-efficacy. Many students in both classes also reported improvements in both physical and mental health, such as weight loss, muscle mass increases, strength increases, and reductions in stress, which were also reflected in our measured data and concurred with previous CrossFit and weight training research [5,8,10,11,13]. However, only one study has previously shown evidence to suggest CrossFit could improve mental health outcomes of adolescents [9].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, weight training programs have improved adolescents' self-efficacy (e.g., confidence in their ability to accomplish a task), self-esteem, self-perceptions, and overall confidence [19][20][21], which was reflected in our findings for increased confidence and self-efficacy. Many students in both classes also reported improvements in both physical and mental health, such as weight loss, muscle mass increases, strength increases, and reductions in stress, which were also reflected in our measured data and concurred with previous CrossFit and weight training research [5,8,10,11,13]. However, only one study has previously shown evidence to suggest CrossFit could improve mental health outcomes of adolescents [9].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, while the classes varied in focus, the use of the CrossFit template underlying both resulted in similar improvements for students in each class. These results support previous research findings for the positive impacts of CrossFit [5], including improvements in aerobic capacity [8] and physical fitness [10,11]. Given the consensus on each of these forms of training to improve athletic ability, future research should focus more on the behavioral factors and outcomes due to the limited existing literature.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation